CO2 Emission Compensation by Tree Species in Some Urban Green Areas - Fornaciari, Marco; Muscas, Desirée; Rossi, Federico; Filipponi, Mirko; Castellani, Beatrice; Di Giuseppe, Alessia; Proietti, Chiara; Ruga, Luigia; Orlandi, Fabio (Sustainability, 2024)
Mitigating the negative impacts of climate change in urban areas has recently become essential to improving citizens’ living conditions. Trees are one of the most effective ways to attenuate the Heat Island phenomenon in cities, and numerous projects have been carried out to calculate tree ecosystem services (ES) provisioning. Among these, the Clivut European project (LIFE 18 GIC/IT/001217) developed a web app to allow citizens and the public administration to quantify the ES provided by the most common tree species. The present study aims to consider a new model to calculate the tree evapotranspiration cooling effect in the urban environment in terms of CO2-compensated emissions. The model directly converts the surface temperature change produced by tree evapotranspiration into the corresponding CO2 offset in four urban parks in two Italian cities (Bologna and Perugia). The considered parks stored 1100 t of CO2 at the time of the study, while the CO2 compensated is 860 t, showing the significance of this interpretation. As a result of the study, it can be concluded that the presented model will allow a better estimation of the potential trees’ climate change compensation and also add further functionality to the web app.